Analisis Keputusan Nasabah Memilih KUR Mikro Berdasarkan Kualitas Layanan dan Promosi pada PT Bank Sumsel Babel KC Palembang - Reynalza Anggri Septi; Paisal Paisal; Hendra Sastrawinata (Jurnal Manajemen Bisnis Era Digital, 2025)
The purpose of this study is to determine the extent to which the relationship between quality and promotion influences customer decisions in selecting Micro People's Business Credit (KUR) products at PT Bank Sumsel Babel KC Palembang. This study applies a quantitative approach, where the entire population consists of 765 customers, with 88 people being sampled through a purposive sampling technique. The data sources used in this study include primary and secondary data, obtained through direct interviews with related parties and the distribution of questionnaires to respondents who have met the research criteria. To analyze the data, a series of instrument feasibility tests, classical assumption tests, and data processing using multiple linear regression analysis were conducted. This analysis includes a t-test (partial), F-test (simultaneous), and the coefficient of determination (R²) to measure the strength of the influence of the independent variables on the dependent variable. Based on the results of the analysis, it was found that both service quality and promotion have a positive and significant influence on consumer decisions, both partially and simultaneously. This indicates that the better the service quality and the more effective the promotion, the higher the tendency of consumers to decide to choose KUR Micro products. The coefficient of determination (R²) of 0.894 indicates that 89.4% of customer decisions can be explained by service quality and promotions, while the remaining 10.6% is influenced by other factors not examined in this study, such as economic conditions, personal experience, recommendations from third parties, and psychological factors. These results provide an important influence for bank management in developing more targeted service and promotion strategies. The results of this study can also serve as a basis for strategic policy-making in developing banking products based on customer needs.